An updated look at actin dynamics in filopodia. Issue 2 (February 2015) - Leijnse, Natascha; Oddershede, Lene B.; Bendix, Poul M.
<x xml:space="preserve">Abstract</x> Cells dynamically interact with and probe their environment by growing finger‐like structures named filopodia. The dynamics of filopodia are mainly caused by the actin rich core or shaft which sits inside the filopodial membrane and continuously undergoes changes like growth, shrinking, bending, and rotation. Recent experiments combining advanced imaging and manipulation tools have provided detailed quantitative data on the correlation between mechanical properties of filopodia, their molecular composition, and the dynamic architecture of the actin structure. These experiments have revealed how retrograde flow and twisting of the actin shaft within filopodia can generate traction on external substrates. Previously, the mechanism behind filopodial pulling was mainly attributed to retrograde flow of actin, but recent experiments have shown that rotational dynamics can also contribute to the traction force. Although force measurements have indicated a step‐like behavior in filopodial pulling, no direct evidence has been provided to link this behavior to a molecular motor like myosin. Therefore, the underlying biochemical and mechanical mechanisms behind filopodial force generation still remain to be resolved. © 2015 Wiley Periodicals, Inc.